2003
DOI: 10.1038/sj.cdd.4401161
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of chromosomal DNA during apoptosis

Abstract: Apoptosis is often accompanied by degradation of chromosomal DNA. CAD, caspase-activated DNase, was identified in 1998 as a DNase that is responsible for this process. In the last several years, mice deficient in the CAD system have been generated. Studies with these mice indicated that apoptotic DNA degradation occurs in two different systems. In one, the DNA fragmentation is carried out by CAD in the dying cells and in the other, by lysosomal DNase II after the dying cells are phagocytosed. Several other end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
284
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(303 citation statements)
references
References 107 publications
6
284
0
7
Order By: Relevance
“…Since chromosome fragmentation is also known to occur during programmed cell death (Nagata et al, 2003), we examined if cells treated with WEE1i showed signs of apoptosis. Western-blot analysis of Caspase 3 and PARP integrity showed no evidence for their proteolytic cleavage within the timeline of chromosomes pulverization ( Figure S3D, data not shown).…”
Section: Dna Fragmentation Upon Wee1 Inhibition Is Not Caused By Rpa mentioning
confidence: 99%
“…Since chromosome fragmentation is also known to occur during programmed cell death (Nagata et al, 2003), we examined if cells treated with WEE1i showed signs of apoptosis. Western-blot analysis of Caspase 3 and PARP integrity showed no evidence for their proteolytic cleavage within the timeline of chromosomes pulverization ( Figure S3D, data not shown).…”
Section: Dna Fragmentation Upon Wee1 Inhibition Is Not Caused By Rpa mentioning
confidence: 99%
“…Nuclear degradation during UV-induced apoptosis is marked by internucleosomal DNA cleavage executed by caspaseactivated DNAse (CAD). 31,32 Defects in nuclear degradation during epidermal cornification were not reported in CADdeficient mice. 31 The nucleus is not completely degraded during apoptosis, as nuclear fragments are detectable in the apoptotic bodies that are cleared by uptake by other cells.…”
Section: Nuclear Eventsmentioning
confidence: 99%
“…31,32 Defects in nuclear degradation during epidermal cornification were not reported in CADdeficient mice. 31 The nucleus is not completely degraded during apoptosis, as nuclear fragments are detectable in the apoptotic bodies that are cleared by uptake by other cells. The DNA is further broken down after engulfment.…”
Section: Nuclear Eventsmentioning
confidence: 99%
“…8 Recombinant mouse AIF can induce purified nuclei to undergo chromatin condensation and 'largescale' DNA fragmentation (to B50 kBp), yet has little or no effect on naked DNA or heat-inactived (561C, 30 min) nuclei, indicating that it has to interact with (an)other protein(s) to cause DNA degradation. 1 In contrast, the oligonucleosomal 'ladder type' of DNA fragmentation is mostly mediated by caspase-activated DNAse, lysosomal DNAse II, 9 as well as endonuclease G, another mitochondrial protein that translocates to the nucleus upon apoptosis induction. 10 In C. elegans, AIF has been shown to interact with endonuclease G, both in genetic and in biochemical terms.…”
mentioning
confidence: 99%